2007
DOI: 10.1093/humrep/del506
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst biopsy versus cleavage stage biopsy and blastocyst transfer for preimplantation genetic diagnosis of β-thalassaemia: a pilot study

Abstract: This pilot study suggests that trophectoderm biopsy and blastocyst transfer may be more advantageous than cleavage stage biopsy with respect to outcome of PGD for monogenic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 47 publications
4
98
1
1
Order By: Relevance
“…At present, blastocyst stage is the optimal time to perform biopsies for preimplantation genetic testing [10]. Trophectoderm biopsies do less harm to development of the embryo [20], while blastocyst biopsy can obtain multiple trophectoderm cells, resulting in an increased number of DNA copies in the biopsy specimen, and therefore more accurate results compared with a single blastomere cell [21]. In our study, we also found that there were less noisy results at blastocyst stage than that at cleavage stage.…”
Section: Discussionsupporting
confidence: 58%
“…At present, blastocyst stage is the optimal time to perform biopsies for preimplantation genetic testing [10]. Trophectoderm biopsies do less harm to development of the embryo [20], while blastocyst biopsy can obtain multiple trophectoderm cells, resulting in an increased number of DNA copies in the biopsy specimen, and therefore more accurate results compared with a single blastomere cell [21]. In our study, we also found that there were less noisy results at blastocyst stage than that at cleavage stage.…”
Section: Discussionsupporting
confidence: 58%
“…It was recently suggested that a trophectoderm biopsy from a day 5 blastocyst has a less harmful effect on further embryonic development compared to blastomere biopsy of day 3 cleavage-stage embryos [3,8,11,44,45]. Scott et al identified blastocyst-stage biopsy as a procedure that does not affect embryo viability and implantation potential as opposed to blastomere biopsy [4].…”
Section: Discussionmentioning
confidence: 99%
“…Removing a few cells from the trophectoderm while leaving the ICM undisturbed in theory has the potential for less adverse effects on the developing embryo and the advantage of providing more cells for analysis, than blastomere biopsy. A study by Kokkali et al [13] demonstrated an improved implantation rate with blastocyst biopsy over cleavage biopsy and subsequent studies support these findings [14].…”
Section: Trophectoderm Biopsy and Improved Methods For Pgs And Pgdmentioning
confidence: 90%